ANALYSIS OF THE IMPLEMENTATION OF ISO/IEC 27001:2013 STANDARDS IN PT. SULSELBAR BANK - Gala, Kristian; Suwandaru, Rahman; Anshar, Muh. Ashary (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to examine the implementation of the ISO/IEC 27001:2013 standard in optimizing the information security system at PT. Bank Sulselbar. This international standard is the main reference in information security management which includes structured policies, procedures, and technical controls to protect the confidentiality, integrity, and availability of data. This study uses a descriptive qualitative approach with a focus on analyzing the implementation and effectiveness of the ISO/IEC 27001:2013 standard and identifying potential weaknesses in the company's information security system. The main object of the study is how the information security management system (ISMS) based on ISO/IEC 27001:2013 has been implemented in the operational environment of Bank Sulselbar. Data were collected through interviews, observations, and documentation studies of work units relevant to information security. The results of the study indicate that PT. Bank Sulselbar has implemented an ISO/IEC 27001:2013-based ISMS in a systematic and structured manner, which includes security policies, risk assessments, access control, and continuous monitoring and evaluation of the system. This implementation has been proven to increase the level of company information protection and strengthen resilience to cyber threats. However, this study also identified several weaknesses, including aspects of human resource awareness of the importance of information security and the need for increased periodic training. Thus, the implementation of ISO/IEC 27001:2013 has made a significant contribution in optimizing the information security system at PT. Bank Sulselbar, but continuous improvement is still needed in several aspects to achieve optimal effectiveness.